2021
DOI: 10.1002/ijc.33808
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome‐wide association study identifies novel candidate susceptibility genes for prostate cancer risk

Abstract: A large proportion of heritability for prostate cancer risk remains unknown. Transcriptome‐wide association study combined with validation comparing overall levels will help to identify candidate genes potentially playing a role in prostate cancer development. Using data from the Genotype‐Tissue Expression Project, we built genetic models to predict normal prostate tissue gene expression using the statistical framework PrediXcan, a modified version of the unified test for molecular signatures and Joint‐Tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…This work can complement findings from other large transcriptome-wide association studies that have also identified potential prostate cancer susceptibility loci, but lack detail about treatment exposure and clinical outcome. 31,32 Among participants with identified EHR data evidence of RP and biopsy, clinical-practice databased algorithms reliably identified treatment timing and sequence, achieving 97.9% concordance for the timing of RP and 86.0% concordance for diagnosis among participants who had GC calculated from a biopsy specimen. Moreover, through pharmacy records and claims, we were able to quantify the duration of systemic therapy and account for time-dependent exposures to systemic therapy, which can be leveraged for larger-scale pharmacogenomic study in prostate cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work can complement findings from other large transcriptome-wide association studies that have also identified potential prostate cancer susceptibility loci, but lack detail about treatment exposure and clinical outcome. 31,32 Among participants with identified EHR data evidence of RP and biopsy, clinical-practice databased algorithms reliably identified treatment timing and sequence, achieving 97.9% concordance for the timing of RP and 86.0% concordance for diagnosis among participants who had GC calculated from a biopsy specimen. Moreover, through pharmacy records and claims, we were able to quantify the duration of systemic therapy and account for time-dependent exposures to systemic therapy, which can be leveraged for larger-scale pharmacogenomic study in prostate cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by including the majority of participants undergoing GC testing in the clinical-practice setting, the participants included in this linkage are demographically representative of those tested in the contemporary era. This work can complement findings from other large transcriptome-wide association studies that have also identified potential prostate cancer susceptibility loci, but lack detail about treatment exposure and clinical outcome …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, genomewide association studies (GWAS) have identified several hundred common genetic risk loci for each of three prevalent cancer types: breast, colorectal, and prostate [5][6][7][8] , and several dozen risk loci have been identified for other cancers, such as cancer of lung, pancreas, and ovarian [9][10][11][12][13] . Previous research, including our work, has identified hundreds of putative cancer susceptible genes potentially regulated by these risk variants, using methods such as expression quantitative trait loci (eQTL) analysis [8][9][10][11][12][14][15][16][17][18][19][20] and transcriptome-wide association studies (TWAS) 7,19,[21][22][23][24][25][26][27][28][29] . However, most dysregulated gene expression has not been thoroughly investigated at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up expression quantitative trait locus (eQTL) studies have begun to explore putative regulatory targets of PrCa risk SNPs ( Thibodeau et al, 2015 ; DeRycke et al, 2019 ). Recent methodological advancements in colocalization of disease-associated SNPs and eQTLs have yielded powerful transcriptome-wide association study (TWAS) approaches to disease-gene discovery, which have been highly successfully in translating single-SNP GWAS hits into gene-level associations with PrCa risk ( Mancuso et al, 2018 ; Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%